2007
DOI: 10.1161/01.res.0000262655.16373.37
|View full text |Cite
|
Sign up to set email alerts
|

Early Exercise Training Normalizes Myofilament Function and Attenuates Left Ventricular Pump Dysfunction in Mice With a Large Myocardial Infarction

Abstract: Abstract-The extent and mechanism of the cardiac benefit of early exercise training following myocardial infarction (MI) is incompletely understood, but may involve blunting of abnormalities in Ca 2ϩ -handling and myofilament function. Consequently, we investigated the effects of 8-weeks of voluntary exercise, started early after a large MI, on left ventricular (LV) remodeling and dysfunction in the mouse. Exercise had no effect on survival, MI size or LV dimensions, but improved LV fractional shortening fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
115
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(134 citation statements)
references
References 62 publications
18
115
1
Order By: Relevance
“…Both diseases are also characterized by a high incidence of VT and SCD. Interestingly, exercise training after myocardial infarction, which normalizes the increased myofilament Ca 2+ sensitivity (47), also has been shown to reduce mortality and the rate of ventricular arrhythmias in animal (48,49) and human studies (50). Further, treatment with the Ca 2+ sensitizer levosimendan significantly increased the incidence of VT in patients with heart failure (51).…”
Section: Discussionmentioning
confidence: 99%
“…Both diseases are also characterized by a high incidence of VT and SCD. Interestingly, exercise training after myocardial infarction, which normalizes the increased myofilament Ca 2+ sensitivity (47), also has been shown to reduce mortality and the rate of ventricular arrhythmias in animal (48,49) and human studies (50). Further, treatment with the Ca 2+ sensitizer levosimendan significantly increased the incidence of VT in patients with heart failure (51).…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic parameters are determined in terminal experiments in anesthetized and ventilated mice (238,551) or rats (540) by advancing a micro-tipped pressure transducer or a combined pressure-volume catheter through the right common carotid artery into the ascending aorta and subsequently into the LV. The positive and negative rates of pressure development and the systolic and enddiastolic pressures may be used as sensitive indicators of thyroid hormone-dependent changes in expression of contractile proteins and proteins involved in intracellular calcium homeostasis.…”
Section: And Recommendation 50bmentioning
confidence: 99%
“…7, 17 But the molecular mechanisms that mediate the powerful cardioprotective effect of EP remain to be elucidated. Several studies have shown that EP increased the expression of some myocardial proteins, such as heat shock proteins, 18 mitochondrial and sarcolemmal ATP-sensitive potassium channels (mitoKATP or sarcKATP), 19 cyclooxygenase-2, 20 and endoplasmic reticulum stress proteins, 7 which can attenuate many types of heart injuries.…”
Section: Ep-induced Early and Late Phase Of Cardioprotection Is Assocmentioning
confidence: 99%